Monitoring the Chemical Composition of Polyolefins along the Molar Mass Axis with High-Temperature Size Exclusion Chromatography Coupled with an Infrared Detector (HT SEC-IR5) - Aboelanin, H.M.; Deshmukh, S.; Macko, T.; Arndt, J.-H.; Podzimek, Štěpán; Bruell, R. (My University, 2023)
Series of ethylene/1-alkene and ethylene-propylene-diene copolymers were separated with size exclusion chromatography (SEC) at 150 °C using 1,2,4-trichlorobenzene as the mobile phase. Methyl (CH3-) and methylene (-CH2-) groups in the separated polymer samples were monitored at specific wavelengths via a filter-based infrared detector (IR5). It was found that the ratio of CH3/CH2 may increase, be constant, decrease or change irregularly along the molar mass axis, depending on the sample under investigation. Because the CH3/CH2 profiles may be very different even for a given series of copolymers synthesized with the same catalyst, it is supposed that one or more experimental parameters, which were not strictly controlled throughout synthesis, are responsible for these substantial differences in the chemical composition along the molar mass axis.
Sledování chemického složení polyolefinů v závislosti na molární hmotnosti pomocí vysokoteplotní gelové permeační chromatografie spojené s infračerveným detektorem
Keywords: Polyolefins; FTIR, chemical composition; size exclusion chromatography; Polyolefiny; FTIR; chemické složení; gelová permeační chromatografie